EXPERT CONCLUSION OF THE SOCIETY OF CARDIOLOGY OF THE RUSSIAN FEDERATION, RUSSIAN NATIONAL SOCIETY OF ATHEROSCLEROSIS, RUSSIAN SOCIETY OF CARDIOSOMATIC REHABILITATION AND SECONDARY PREVENTION ON STATIN THERAPY OPTIMIZATION IN CLINICAL PRACTICE (Рациональная фармакотерапия в кардиологии)
Заключение экспертов.